Access to radiotherapy among circumpolar Inuit populations. Issue 10 (October 2019) - Chan, Jessica; Friborg, Jeppe; Chernov, Mikhail; Cherkashin, Mikhail; Grau, Cai; Brundage, Michael; Slotman, Ben
Summary: Cancer is a substantial health burden for Inuit populations, an Indigenous peoples who primarily inhabit the circumpolar regions of Alaska, Canada, Greenland, and Russia. Access to radiotherapy is lacking or absent in many of these regions, despite it being an essential component of cancer treatment. This Review presents an overview of factors influencing radiotherapy delivery in each of the four circumpolar Inuit regions, which include population and geography, health-systems infrastructure, and cancer epidemiology. This Review also provides insight into the complex patient pathways needed to access radiotherapy, and on radiotherapy use. The unique challenges in delivering radiotherapy to circumpolar Inuit populations are discussed, which, notably, include geographical and cultural barriers. Recommendations include models of care that have successfully addressed these barriers, and highlight the need for increased collaboration between circumpolar referral centres in Alaska, Canada, Greenland, and Russia to ultimately allow for better delivery of cancer treatment.